The Principles of Justice and Legal Assurance in Choice of Law for International Electronic Contract - Moh. Ali (Hang Tuah Law Journal, 2017)
Along with globalization, legal relationships between parties are not exclusively domestic since it also involves foreign element. As the result, it affects the usage of different legal systems in establishing a contract. Unlike commercial contracts in which the position between parties is equal, consumer contracts place the consumers unequally resulting in lameness and disproportion among consumers in terms of conveying a common will to choose the clauses of contract. The existence of injustice causes a key paradigm shift on contractual freedom from” both-sided autonomy” to “one-sided autonomy.” Additionally, legal uncertainty will also appear particularly on the tug-of-use of the sea point based on whether unilateral, multilateral, or substantive choices of law. Such condition requires harmonization as necessity along with the legal context increasingly global.